Impact-Based Critical Areal Rainfall for Early Flood Warning: A Case Study of Zhulong River Watershed in the Upper Reaches of the Xiong’an New Area - Lili Si; Liang Zhao; Ziyan Chen; Xiaolei Chen; Tiesong Zhao; Wenjuan Xie; Bingwei Wang; Yanjun Wang (Atmosphere, 2023)
In this work, the largest tributary of the South Branch in the upper reaches of the Xiong’an New Area is selected as the study area. The impact-based critical areal rainfall indices for early flood warnings are proposed from the perspective of the impacts of floods on socio-economic factors. Specifically, four steps, including the determination of the damage-causing discharges, the establishment of the rainfall–discharge relationship, the computation of the critical areal rainfall and the validation of the early warning indices, were used to determine the critical areal rainfall for early flood warnings in the watershed. The results showed that the 1-day critical areal rainfall amounts were 31 mm, 63 mm, 92 mm and 160 mm for early flood warning levels 4, 3, 2 and 1, respectively, when the 1-day antecedent areal rainfall was ≤10 mm. The critical areal rainfall amounts were 20 mm, 54 mm, 87 mm and 160 mm for early flood warning levels 4, 3, 2 and 1, respectively, when the 1-day antecedent areal rainfall was >10 mm. The early warning effectiveness of the proposed critical indices was validated with historical catastrophic flood events and precipitation data during recent flood seasons. The results demonstrated that the impact-based critical indices had a high accuracy and could release warnings 1–2 days in advance, which could effectively avoid the occurrence of missed and underestimated warnings.